Annual Plan 2003-04 Government of Goa - Planning Commission (Planning Commission, 2003)
The Annual Plan 2003-04 assumes Special significance as there has been a total review of plan schemes and programmes. in pursuance to the Tenth Plan guidelines of the Planning Commission, the State had initiated this massive exercise while formulating the Tenth Five Year Plan itself. This has to be a continuous exercise so as to ensure that the State resources are utilized optimally and judiciously for the fullest benefit of the people.
Directorate of Planning, Statistics and Evaluation, Government of Goa